Examining accuracy in students' spoken and written english language via digital story telling - Nor Nadia Raslee (Kulliyyah of Education, International Islamic University Malaysia, 2020)
The objective of this study is to investigate how Digital Storytelling helped enhance learners' language accuracy, and the learners' perceptions on Task Condition and Task Difficulty in implementing Digital Storytelling. The impetus of this study is rooted in issues such as graduate employability, and poor English proficiency in Malaysia especially among school leavers. The researcher sought to understand the phenomena by exploring areas such as English as a second language and language learning motivation. There have been numerous researches in the areas of English as a second language, language proficiency, the language skills and learner motivation. However, not enough is known about the spoken and written accuracy of language production in the Malaysian context. The theory that guides this study is the Cognition Hypothesis that consist of the elements in task design such as Task Complexity, Task Condition and Task Difficulty. The task selected to explore language accuracy and task-based approach was Digital Storytelling. 55 students in an ESL course were selected as participants. Participants developed their Digital Storytelling over ten weeks. To obtain rich and thick data, data was triangulated via reflective journal entries and vlog. Then, the data was analysed via thematic and document analysis to investigate written and spoken accuracy and, explore how participants respond to the elements in Task Condition and Task Difficulty. The findings revealed insightful results. In terms of language accuracy, it was found that both written and spoken accuracy were not impactful. In the 14th week of the task, 13 errors were identified in written language, while 14 errors were found in spoken language. Errors such as subject-verb agreement, sentence structure, and first language interference were present in both language production. 7 themes within the Task Condition dimension elucidated participants' experiences while, 7 themes outlined their experiences within Task Difficulty. Additionally, the findings revealed the potential of Digital Storytelling as a powerful pedagogical tool in preparing learners with the 21st century skills, and engaging learners' in enhancing their soft skills, teamwork, engagement, creativity, and motivation.